Casná diagnostika ankylozující spondylitidy - Pavelka, K (Vnitrni lekarstvi, 2006)
The present study surveys the problems of diagnostics of early ankylosing spondylitis (AS) and axial spondylarthritis (SpA). Epidemiologic studies repeatedly identified seven- to nine-year delay of diagnosis of AS from its development to its first manifestations. Delayed diagnostics is caused both by unfamiliarity of rheumatologists with the disease and the inappropriateness of New York classification criteria for early stages of AS. In this study, we suggest diagnostic algorithms allowing high probability diagnosis of AS/axial in X-ray silent stage (the so-called pre X-ray stage). Spondylarthritis represents approximately 5% of a total number of chronic low back pain (CLBP) cases. The probability grows up to 15% with the presence of inflammatory character of back pain. The presence of HLA B 27 increases the probability to 59% and the occurrence of other 1 or 2 clinical signs raises the probability up to 90%. Probability reaches 95% with positive MRI. The overall concept requires verification of new samples in a prospective study. After certification of such study, it will be possible to use biological medications for much more efficient therapy of patients in early AS stages.
Keywords: Spondylarthritis; Early Diagnosis; Spondylitis, Ankylosing; ankylózující spondylitida; Humans; spondylartritida; časná diagnóza; lidé